Hibridación en algunas poblaciones de Artemia franciscana (Anostraca: Artemiidae) - Correa Sandoval, Francisco; Bückle Ramírez, Luis Fernando; de la Rosa Vélez, Jorge (Revista de Biología Tropical, 1993)
The fertility within and among two Mexican and two San Francisco Bay populations of Artemia franciscana was assayed. Mexican strains belong to the sarne species. The whole F1 is internally fertile, though sorne F2 hybrids, in which a Mexican variety was involved, showed a low resislence to Vibrio infections